Pengembangan Worksheet Berorientasi Guided Inquiry untuk Membentuk dan Melatih Habits of Mind Mahasiswa - Masiah, Masiah; Adawiyah, Siti Rabiatul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2018)
This study aims to develop a guided inquiry that is valid and effective so that it can shape and train students’ habits of mind. This research is research and development (R & D) with steps; observation of potential problems, product design, design validation, limited scale trials, product design revisions, large-scale trials. Worksheet validation is done by 2 validators with 4.2 validation results with a valid category. The results of the study on the implementation test on 12 students showed the results of the N-Gain test of 0.73 with high categories and the habits of mind of students assessed through questionnaires had an average score of 74.5 in the good category. The results of the habits of mind observation of students showed an increase from the first meeting to the last meeting. Based on the results of the study it can be concluded that guided inquiry-oriented guided inquiry development is valid and effective to train and form the habits of mind of students. Research findings also indicate a positive correlation between habits of mind and student learning outcomes.